(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article —based on the premise that a film adaptation is the result of the reading, interpreting and understanding of a literary text— is a study of the relationship between the short story entitled ¿Qué me quieres amor?, by Spanish writer Manuel Rivas, and the film, La lengua de las mariposas, directed by José Luis Cuerda. Thus, the integration of three short stories by Rivas, the quotations, the references and the clarifications introduced in the movie by José Luis Cuerda, and the script writer, Rafael Azcona, into one reading, present a dialogue —compared by Manuel Rivas with a transmigration— which speaks of a certain way of interpreting Spain´s recent history.